The Effect of The Use of Gloves on Complaints of Skin Disorders (Dermatitis) in Fish Sorting Workers in Fish Auction Places (TPI) at Pantai Labu District - Raisha Octavariny (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Health is a right for workers who are in the formal and informal sectors, as well as fishermen who especially work in the fish sorting section are very vulnerable to skin diseases. This is because most fishermen do not want to use gloves while working due to inconvenience reasons. Prevention efforts that can be done by implementing a work system using gloves starting from the beginning of work until the end of work. The purpose of this study was to determine the effect of using gloves on complaints of skin disorders (dermatitis) in fish sorting workers at the fish auction place (TPI) Pantai Labu District. This type of research is a quantitative study with a quasi-experimental approach to the research design of one group pretest posttest. Using the Purposive Sampling technique with a sample of 32 respondents. Data collection using the Observation sheet. The statistical test in this study used the Wilcoxon test to see the difference in the average results between the pre-test and post-test. The average difference in complaints of skin disorders (dermatitis) before being given an intervention was 2.31 and after being given an intervention of 1.84, which means that there was a significant effect on reducing complaints of skin disorders in workers. The results of this study indicate that there is an effect of using gloves on complaints of skin disorders (dermatitis) in workers in the fish sorting section at the fish auction place (TPI) Pantai Labu District with the results (p = 0.000 < 0.05). Workers should get used to using gloves. hands while working, To minimize complaints of skin disorders (dermatitis) that are felt so that workers are more productive in doing their work.